Analysis of Tertiary Learners’ Writing Errors through Surface Strategy Taxonomy - Kharence Grell Laquiao Dagson (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study analyzed grammatical errors in the descriptive writing of Bachelor of Secondary Education major in English (BSEd-English) students from private higher education institutions (HEIs) in Kalinga Province using the Surface Strategy Taxonomy (SST) by Dulay, Burt, and Krashen. It aimed to identify error types, determine prevalent patterns, and examine factors contributing to learners’ writing difficulties. Guided by Error Analysis Theory, the study employed a descriptive qualitative design and collected data from second- and third-year BSEd-English students during the first semester of Academic Year 2025–2026 through purposive sampling. Findings revealed 383 grammatical errors with misformation (46.74%) and addition (40.99%) as the most frequent, while omission (9.92%) and misordering (2.35%) were less common. Misformation and addition errors—particularly in word choice, singular–plural forms, verb tenses, pronouns, and lexical devices—reflect learners’ struggles with grammar, vocabulary, and sentence construction. Influencing factors included interlingual interference, intralingual transfer, pedagogical, and psychological issues emphasizing the need for improved instruction and feedback. To address these issues, a writing instrument for pre-admission evaluation was developed to strengthen grammar and writing proficiency among incoming English majors. The results provided insights for language instruction, curriculum development, and teacher education policy supporting quality education aligned with Sustainable Development Goal (SDG) 4.